Improvement of magnetic and cryogenic energy preservation performances in a feeding-power-free superconducting magnet system for maglevs. (1st January 2020) - Dong, Fangliang; Huang, Zhen; Xu, Xiaoyong; Hao, Luning; Shao, Nan; Jin, Zhijian
Abstract: This work relates to improvement of magnetic and cryogenic energy preservation performances in an on-board high-temperature superconducting magnet system used in linear synchronous motors for ultrahigh speed maglevs. Since maglevs remove all the physical contacts to the ground, the wireless on-board feeding power is rather limited especially for superconducting subassemblies. And it has become one of the development bottlenecks. For the magnet system, realization of on-board feeding-power free is pivotal, which is regarding to two important energy conversions: electrical to magnetic energy by persistent-current mode of superconductivity, and latent heat to effective cooling (or cryogenic) energy by α-β phase transition of solid nitrogen (SN2 ) in the system. Improvements of the two energy conversions are the main work. Firstly, model and numerical approach of persistent-current mode are proposed, followed by simulation of SN2 cooling. Then performances of persistent-current mode and cryogenic energy preservation are reported. Energy conversion efficiency is also analyzed for a strategy to improve cooling performance. The strategy successfully extends cryogenic energy preservation time to 8.83 h and suppresses thermal non-uniformity to <0.1 K. The enhanced cooling performance is also reflected in a prolonged persistent-current mode lasting for 8.17 h. The work demonstrates the applicability of the magnet system. Highlights: A novel HTS magnet system able to preserve magnetic and cryogenic energy. On-board feeding power is liberated for operation of the HTS magnet system. Persistent current mode is reliable with prolonged retaining time. Thermal uniformity of solid nitrogen cooling preservation is excellent.